Thermodynamic modeling of a solar energy based combined cycle with rock bed heat storage system - Ozturk, Merve; Dincer, Ibrahim; Javani, Nader (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In the current study, a combined system which consists of gas and steam turbines supported by concentrating solar receiver is studied through a thermodynamic approach using energy and exergy methods. Because of the intermittent nature of solar energy, a rock bed thermal energy storage system is incorporated into the system. The rock bed storage allows the secondary cycle to operate independently in order to generate electricity at night or once the solar energy is not available. Charging capacity of the rock bed is 9 MW for an 8 h period of time. The rock bed stores thermal energy for 4 h and thereafter, discharges it to run the steam cycle for 12 h. The energy and exergy efficiencies of the system are investigated through specific parametric studies to examine the effects of changing state properties and working conditions on energy and exergy efficiencies. According to the performance evaluation, the gas turbine could generate 3.87 MWe power while 1.76 MWe power is generated by the steam turbine. The overall energy and exergy efficiencies are obtained to be 69.2% and 37.3%, respectively.
Keywords: Efficiency; Exergy; Rock bed storage system; Solar energy; Thermal energy storage; THERMAL STORAGE; TES SYSTEMS; POWER; PERFORMANCE; WATER; Energy & Fuels